Changes in the linear relationship of ENSO–PDO under the global warming. (17th May 2012) - Kwon, MinHo; Yeh, Sang‐Wook; Park, Young‐Gyu; Lee, Yoon‐Kyoung
Abstract We examine changes in El Niño and Southern Oscillation (ENSO)/Pacific Decadal Oscillation (PDO) relationship under the global warming using coupled climate models participated in the Intergovernmental Panel on Climate Change (IPCC) Fourth Assessment Report (AR4). The temporal structure for the ENSO–PDO relationship is changed remarkably. The relationship between ENSO and PDO during the boreal winter (December, January and February) becomes stronger so that there would be more frequent in phase occurrence of ENSO and PDO (i.e. El Niño—a positive phase of PDO or La Niña—a negative phase of PDO). As PDO could constructively interfere with the ENSO‐related climate when ENSO and PDO are in phase, in the future one may expect stronger climate signal because of ENSO in the midlatitude. The IPCC AR4 model also shows that the Pacific North America‐like pattern is slightly shifted eastward and much stronger. We also discuss the possible reason for these changes. Copyright © 2012 Royal Meteorological Society